LKPD BERBASIS MODEL PEMBELAJARAN ICARE KELAS VIII SMPN 31 PADANG - Fitri Yanna; Masril Masril; Yurnetti Yurnetti (PILLAR OF PHYSICS EDUCATION, 2018)
Competence of student grade 8th SMPN 31 Padang is still below to passing grade (KKM), because of teaching and learning materials conducted to student learning was still centered on the teacher. This study was   to try to determine the effect of LKPD based on the ICARE learning. To improve of student competence at science concept: motion by thing and living thing at grade 8th SMPN 31 Padang. This type of research is Quasi Experiment Designs with Randomized Control Group Only Design. In this study all students grade 8th SMPN 31 Padang Academic Year 2017/2018 and sampling technique was Purposive Sampling, and grade 8th.2 as eksperimental group and grade 8th.3 as a control group. The research sample is class VIII 2 and class VIII 3. The data or student competence that are: affective, kognitive, and psychomotor competence. Based on the data analysis, the research found that: the competence student at grade 8th SMPN 31 Padang for three domain that are affective, kognitive and psycomotor.